Abundance, Biomass and Diversity of Soil Fauna at Different Ecosystems in Jakenan, Pati, Central Java - Rahayu Widyastuti (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2004)
The assessment of soil fauna in three different ecosystems namely teak forest, home garden and fallow paddy field had been studied in Pati, Central Java. The soil fauna was collected using a soil corer of 20 cm diameter to the depth of 0-15 cm from 5 randomized points in the above ecosystems. The soil fauna was ten extracted in a Berlese funnel extractor. Soil fauna in the home garden showed the highest abundance (2 940 individual m–), followed by teak forest (2 340 individual m-?) and fallow paddy (1 790 individual m-?). The home garden had also a higher soil fauna diversity (2.06) compared to the teak forest (1.82) and fallow paddy (1.67). In terms of soil fauna biomass, the teak forest had a higher value (961 mg m-3 compared to the home garden (368 mg m-3 and fallow paddy (309 mg m